Mellan etnologi och modern sociologi: K. Rob. V. Wikman som medlare i Finland och Sverige (Sociologisk Forskning, 2008)
Between ethnology and sociology: K. Rob. V. Wikman as a mediator in Finland and Sweden K. Rob. V. Wikman, professor in sociology at the Åbo Akademi University in Turku, Finland, played a central role both within Finnish and Swedish sociology in the 1940s and 1950s. He was a student of Westermarck and thus his own research represented an ethnosociological tradition, which at that time was challenged by modern, American-influenced sociological ideas. The aim of this article is to discuss the adaptation of “modern sociology” and the drawing of boundaries in Nordic sociology after the Second World War by focusing on Wikman’s work in Finnish as well as Swedish sociology, especially the assessor assignments he was given, and by giving emphasis to some of those that served as border poles or border markers in this process. The comparative starting point gives us reason to discuss some nationally characterized similarities and differences that can be observed in the establishment process of modern sociology in Finland and Sweden.